Influence of aerobic and anaerobic interval training compared with yogic practices on selected physical fitness variables of high school football players - A. Prakash**, *S. Senthilkumar and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The aim of this study was to determine whether aerobic interval training with yogic practices (AeIYG) or anaerobic interval training with yogic practices (AnIYG) has greater effect on selected physical fitness variables, speed and agility among high school football players. For this purpose, the investigator selected find out the influence of aerobic and anaerobic interval 90 football players divided into three groups, namely, AeIYG, AnIYG and control group (CG). The subjects were tested for speed and agility initially and after 12 weeks of experiment on respective training on the subjects. The results proved that there was significant improvement in speed (F: 45.52) and agility (F 8.37) on adjusted means, against required F value of 3.1. The post hoc analysis proved that AeIYG was better than CG and AnIYG in improving speed and agility of school level football players. It was concluded that aerobic interval training with yogic practices significantly improved speed and agility of the school level football players than anaerobic power with yogic practices.